2022
DOI: 10.1111/jam.15371
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus sp. and arbuscular mycorrhizal fungi consortia enhance wheat nutrient and yield in the second-year field trial: Superior performance in comparison with chemical fertilizers

Abstract: The aim of the study is to analyse the effect of microbial consortia for wheat biofortification, growth, yield and soil fertility as part of a 2-year field study and compare it with the use of chemical fertilizers. Methods and Results:A field trial (second year) was conducted with various combinations of plant growth-promoting bacteria (PGPB) and arbuscular mycorrhizal fungi (AMF) treatments, ranging from a single inoculant to multiple combinations.The microbial consortia used were Bacillus sp. and AMF based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 86 publications
1
9
0
Order By: Relevance
“…The higher levels of EM increased the mineralization of OM (Anjum and Khan, 2021) and the synthesis of amino acids and protein (Iriti et al, 2019), which in turn increased the crop growth and leaf area (Talaat et al, 2015). The release of phytohormones and growth regulators by EM makes the soil environment favorable for root growth, improving nutrients' uptake (Chen et al, 2018;Yadav et al, 2022), which in turn increasing the net photosynthesis and leaf expansion (Iriti et al, 2019), assimilating formation (Akhtar et al, 2019b) and, consequently, increasing the aboveground biomass production.…”
Section: Discussionmentioning
confidence: 99%
“…The higher levels of EM increased the mineralization of OM (Anjum and Khan, 2021) and the synthesis of amino acids and protein (Iriti et al, 2019), which in turn increased the crop growth and leaf area (Talaat et al, 2015). The release of phytohormones and growth regulators by EM makes the soil environment favorable for root growth, improving nutrients' uptake (Chen et al, 2018;Yadav et al, 2022), which in turn increasing the net photosynthesis and leaf expansion (Iriti et al, 2019), assimilating formation (Akhtar et al, 2019b) and, consequently, increasing the aboveground biomass production.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, AMF strains did not exhibit a complex symbiotic network (Figure 7B), indicating that AMF may strongly affect wheat. Current studies have confirmed that the combination of PGPR and AMF can exert greater growth-promoting characteristics to stimulate plant growth, which is better than inorganic fertilizer (Yadav et al, 2020;Yadav et al, 2021). Therefore, because of the universality of AMF and its potential impact on plant nutrient uptake and growth, it is crucial to verify the effect of biocontrol agents on AMF communities in the field.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the grain number and yield of wheat in the BIO group were significantly higher than those in the CK group ( Table 3 ). The main reason may be increased rhizosphere soil nutrients ( Yadav et al., 2021 ). Concurrently, PGPR and AMF synergistically increase nutrient absorption, enhance photosynthesis, optimize rhizosphere bacteria, and improve soil health.…”
Section: Discussionmentioning
confidence: 99%
“…The results of antimicrobial activity of methanolic extracts from control and AM treated A. paniculata plants are shown in et al, (2011) who proved increase in protein content in wheat grains of AMF inoculated plants (Yadav et al, 2022). Tobacco plants inoculated with AM, alone or in combination with organic amendment, increased plant dry weights and improved phosphorous nutrition considerably (Manoharan et al, 2010).…”
Section: Antimicrobial Activity By Agar Well Diffusion Methodsmentioning
confidence: 99%